SECURITY MANAGEMENT MECHANISM OF ENTERPRISES AT NETWORK STRUCTURES BASED ON A SYSTEMATIC APPROACH AND ECONOMIC AND MATHEMATICAL MODELING (Development Service Industry Management, 2023)
The development of the information society in the conditions of the hybrid war between Ukraine and Russia is affected by the aggravation of international conflicts, the instability of the globalized socio-economic environment, and the aggravation of social and environmental problems. In this regard, Ukrainian enterprises, in particular enterprises of network structures, daily face problematic situations, the solution of which requires the effective functioning of the management system. This involves taking into account the potential of informatization of production and socio-economic processes. Therefore, the purpose of this article is to develop scientific and methodical approaches to making informed management decisions based on the use of economic and mathematical methods and models together with modern information systems and computer technologies. This article defines the important role of the influence of external and internal environmental factors on the management of the enterprise network structure. Mathematical models for evaluating management decisions have been developed. In particular, a mathematical model was built to determine the manager’s level of readiness for managerial decision-making, as well as a model for calculating the coefficients of the manager's readiness for decision-making. A model of managerial decision-making in the conditions of a non-standard situation in complex socio-economic conditions was created, taking into account the possibilities of using information systems and computer technologies, which creates prerequisites for the successful functioning of the administrative system.
Keywords: enterprises of network structures; security management; economic security management; security system; security management mechanism; network modeling; economic-mathematical model; digital transformation